Analysis of TIKA (Turkish Cooperation and Coordination Agency) Data on development aids between 2005-2012, Applied Turkey Sample, - Korkmaz, M., Yücel, A. S., Aytaç, A., (My University, 2014)
One of the most important features arisen by globalization is the fact that all world countries get into a process to affect each other voluntarily or involuntarily. During this process, differences between countries are revealed more clearly and developed countries cannot remain insensitive to the problems of developing countries. At this point, development aids through which inequalities between countries can be, even partially, removed and the impact of existing problems on other countries can be decreased are important for receiver and donor countries. This research aims to determine the changes resulted from development aids by years with the use of data obtained from Turkish Cooperation and Coordination Agency (TIKA) related to development aids made between 2005-2012. The dataset obtained from TIKA was analyzed in Excel program. Within scope of the analysis, frequency and descriptive tables were used. At the end of the research, it was found that total development aids tend to raise in Turkey and the biggest share among the total development aids of 2012 belongs to official stream. In addition, it was found that official development aids raised 97% compared to the previous year; social aids exceeded 16 billion dollars in 2012 and the countries to which the most aids have been sent are Afghanistan and Syria.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: TİKA; Küreselleşme; Yardım; Kalkınma; İşbirliği; Dünya; Türkiye